2001
DOI: 10.1152/ajpgi.2001.281.1.g200
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of CCl4-induced hepatic fibrosis by GdCl3treatment or dietary glycine

Abstract: The role of Kupffer cells in CCl(4)-induced fibrosis was investigated in vivo. Male Wistar rats were treated with phenobarbital and CCl(4) for 9 wk, and a group of rats were injected with the Kupffer cell toxicant gadolinium chloride (GdCl(3)) or were fed glycine, which inactivates Kupffer cells. After CCl(4) alone, the fibrosis score was 3.0 +/- 0.1 and collagen protein and mRNA expression were elevated, but GdCl(3) or glycine blunted these parameters. Glycine did not alter cytochrome P-450 2E1, making it unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
133
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 43 publications
5
133
1
1
Order By: Relevance
“…Several studies have demonstrated that Kupffer cells play a critical role in various forms of liver injury via paracrine interactions with hepatocytes. For example, depletion or inactivation of Kupffer cells diminished injury and fibrosis due to chronic carbon tetrachloride exposure early as well as early alcoholic steatohepatitis (ASH) (16,17,23), without affecting ethanol metabolism (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that Kupffer cells play a critical role in various forms of liver injury via paracrine interactions with hepatocytes. For example, depletion or inactivation of Kupffer cells diminished injury and fibrosis due to chronic carbon tetrachloride exposure early as well as early alcoholic steatohepatitis (ASH) (16,17,23), without affecting ethanol metabolism (24).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that Kupffer cells also play a causal role in fibrogenesis (17). Hepatic fibrosis may occur simultaneously with hepatitis and is characterized by the overproduction of extracellular matrix proteins such as Collagen type I (26).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation triggers liver fibrosis via a signaling event in which liver resident macrophages (Kupffer cells, KC) activate hepatic stellate cells (HSCs) 2 to deposit collagen (1,2). Liver dysfunction results from the fibrotic tissue distorting the liver parenchyma.…”
mentioning
confidence: 99%
“…: 508-856-5275; Fax: 508-856-4770; E-mail: gyongyi.szabo@umassmed.edu. 2 The abbreviations used are: HSC, hepatic stellate cell; IRF3, interferon regulatory factor 3; STING, stimulator of interferon genes; ER, endoplasmic reticulum; ␣-SMA, ␣-smooth muscle actin; IFNAR1, type I IFN receptor; TIR, Toll/interleukin-1R; TRIF, TIR domain-containing adapter-inducing interferon-␤; TRAM, TRIF-related adaptor molecule; TBK1, Tank-binding kinase 1; TLR, Toll-like receptor; LMNC, liver mononuclear cell; H&E, hematoxylin and eosin.…”
mentioning
confidence: 99%
“…In agreement with this hypothesis, deletion of specific components of the inflammatory response modifies or attenuates the fibrotic scar in vivo. It has been demonstrated that Kupffer cell inactivation, 4 B lymphocyte deficiency, 5 or macrophage depletion 6 result in lower scarring and reduced activation of HSCs.…”
mentioning
confidence: 99%